Isoparactis fionae sp. nov. (Cnidaria: Anthozoa: Actiniaria) from Southern Patagonia with a discussion of the family Isanthidae - Lauretta, D.; Häussermann, V.; Brugler, M. R.; Rodríguez, E. (Organisms Diversity & Evolution, 2013)
A new species from Southern Patagonia, Isoparactis fionae sp. nov., is described. Isoparactis fionae sp. nov. differs from other species in the genus by having longitudinal rows of adherent rugae in the column, number of tentacles, cnidae and geographic distribution. We amend the generic position of the previously termed Paraisanthus fabiani (now Isoparactis fabiani comb. nov.), transferring it to Isoparactis as we discovered acontia in the type material of this species. We amend the binomen of Acraspedanthus ferax and use the correct binomen for the species Isoparactis ferax. In addition, we transfer the genus Isoparactis (previously within Bathyphelliidae as Acraspedanthus) to Isanthidae based on molecular evidence and because its diagnosis corresponds better with this family; we amend the diagnosis of Isanthidae accordingly. Finally, we discuss phylogenetic relationships within Isanthidae and among members of the superfamily Metridioidea. Our results show that Isanthidae is composed of derived acontiate sea anemones that have diversified in shallow waters of the Southern Hemisphere and that the family is putatively the sister group of a deep-sea lineage.